Innovations in microchip capillary electrophoresis for the direct detection of biologically important molecules - Vickers, Jonathan A., author; Henry, Charles S., advisor (Colorado State University. Libraries, 2007)
Microchip capillary electrophoresis (MCE) and related techniques have benefits over conventional separation instrumentation, including small size, high speed (seconds time scale), and low sample consumption (pL injection volumes). These features make MCE an attractive separation method, particularly for point-of-measurement applications. This thesis will demonstrate improvements made to MCE coupled to electrochemical detection (EC) in the forms of increased sensitivity through the use of microwire detection electrodes and microwire decoupling electrodes, increased selectivity from the use of multiple detection techniques such as pulsed amperometric detection as well as dual electrode detection and improvements in the materials chemistry through the use of alternate microchip materials. CE and MCE are relatively new separation techniques. CE was first developed by Jorgenson in 1981 and MCE was developed shortly after that in 1992 by Manz. Detection with MCE is most commonly accomplished using laser induced fluorescence (LIF). While LIF detection has the benefit of high sensitivity and low limits of detection it has some drawbacks, including difficulties in miniaturization, portability and higher costs than some detection instrumentation used with microchip CE. EC was later coupled to MCE devices. In contrast to LIF, EC is easily miniaturized and existing instrumentation is already portable. EC, however, has a few inherent problems: high noise levels limit sensitivity and in its most common form, DC amperometry, it is limited to a small number of easily oxidizable or reducible analytes. In my work I systematically addressed these issues by improving the design and construction of EC detection electrodes. I will show that increased sensitivity and decreased detection limits are possible through the incorporation of microwire working electrodes and a microwire decoupler. The incorporation of a palladium decoupler for the isolation of separation current from the detection current allows for decreased background, and in turn, lower detection limits. I will also address the low number of detectable analytes and the lack in selectivity of DC amperometry through the use of pulsed amperometric detection (PAD) and dual electrode detection, respectively. PAD will increase the number of detectable analytes allowing for the direct detection of carbohydrates, amines and thiols. Dual electrode detection will increase selectivity by allowing multiple potentials to be utilized for the selective detection of compound with reversible redox reactions as well as analytes with specific oxidation potentials in complex mixtures. As a final example of the applicability of the chemistry I have developed the direct detection of proteins using hemoglobin, myoglobin, albumin and concanavalin A as models. Materials chemistry is also beginning to play a more important role in MCE because of the use of polymers as substrates. Poly(dimethylsiloxane) (PDMS) has become one of the most widely used materials for microchip capillary electrophoresis and microfluidics. The popularity of this material is the result of its low cost, simple fabrication, and rugged elastomeric properties. The hydrophobic nature and lack of surface stability of PDMS limit its applicability for MCE. The surface of PDMS can be made hydrophilic using a simple air plasma treatment; however, this property is quickly lost through hydrophobic recovery caused by diffusion of unreacted oligomers to the surface. This hydrophobic recovery causes the MCE devices to have poor separation efficiencies and large peak tailing (peak skew). In my work I will address these issues through a simple extraction and oxidation of PDMS as well as exploring alternative microchip materials. PDMS can be extracted in a series of solvents designed to remove unreacted oligomers from the bulk phase. Then the oligomer-free PDMS is oxidized in a simple air plasma, generating a stable layer of hydrophilic SiO2. The extracted oxidized PDMS (EO-PDMS) shows a dramatic increase in separation efficiencies and a decrease in peak skew from 3.2 on native PDMS to 1.2 on EO-PDMS. The introduction of thermoset polyester (TPE) as an alternative microchip material will also be presented. TPE shows promise as a merger between the ease of fabrication and cost effectiveness of PDMS and the higher separation efficiencies and increased surface stability of other polymers such as Poly(methylmethacrylate) (PMMA) and Poly(carbonate) (PC). These benefits will be shown in the form of increased separation efficiencies and decreased peak skews.
Keywords: analytical chemistry